5T4-specific chimeric antigen receptor modification promotes the immune efficacy of cytokine-induced killer cells against nasopharyngeal carcinoma stem cell-like cells - Xueyang Guo (Nature Portfolio, 2017)
Abstract Relapse and metastasis of nasopharyngeal carcinoma (NPC) are presumably attributed to cancer stem cells (CSCs). In recent years, chimeric antigen receptor (CAR)-modified immune effector cells have been shown to have impressive antitumour efficacy. In this study, we aimed to identify appropriate tumour-associated antigens predominantly expressed on NPC stem cells (NPCSCs) and determine their suitability for CAR-engineered cytokine-induced killer (CIK) cell therapy against NPC. By investigating the expression patterns of potential target antigens (ROR1, 5T4 and CAIX) in NPC, we found that the oncofetal antigen 5T4 was predominately expressed in NPC cell lines and tissues but absent in non-cancerous nasopharyngeal tissues. Moreover, significantly enhanced expression of 5T4 in NPC spheroids revealed its relationship with putative NPCSCs. Hence, we designed a CAR construct (5T4-28Z) specific for 5T4 and generated CAR-transduced CIK cells. Our results showed that the artificial CAR was efficiently expressed on the surface of CIK cells and that no native phenotypes were altered by the gene transduction. Functional assays revealed that 5T4-28Z-CIK cells possessed both CAR-mediated and CAR-independent anti-NPC activity and were capable of efficiently attacking NPC cells, especially NPCSC-like cells in vitro, suggesting that they might serve as an attractive tool for developing efficient therapies against NPC.